2017
DOI: 10.1364/boe.8.004729
|View full text |Cite
|
Sign up to set email alerts
|

Automated segmentation and quantification of airway mucus with endobronchial optical coherence tomography

Abstract: Abstract:We propose a novel suite of algorithms for automatically segmenting the airway lumen and mucus in endobronchial optical coherence tomography (OCT) data sets, as well as a novel approach for quantifying the contents of the mucus. Mucus and lumen were segmented using a robust, multi-stage algorithm that requires only minimal input regarding sheath geometry. The algorithm performance was highly accurate in a wide range of airway and noise conditions. Mucus was classified using mean backscattering intensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
0
8
0
1
Order By: Relevance
“…Mucus contrast demonstrated the most significant post‐allergen difference between the AA and AC groups ( P < 0.0001). Although mucus contrast is likely influenced by factors such as cellular debris, we have already demonstrated that mucus contrast correlates with mucin content obtained from BAL . Although further tests are necessary to establish correlations, this metric seems to accurately capture the appearance of mucus in our images (refer to the more solid appearing mucus in the AA airways of Figs ).…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Mucus contrast demonstrated the most significant post‐allergen difference between the AA and AC groups ( P < 0.0001). Although mucus contrast is likely influenced by factors such as cellular debris, we have already demonstrated that mucus contrast correlates with mucin content obtained from BAL . Although further tests are necessary to establish correlations, this metric seems to accurately capture the appearance of mucus in our images (refer to the more solid appearing mucus in the AA airways of Figs ).…”
Section: Discussionmentioning
confidence: 71%
“…OCT images were processed according to standard processing techniques . Four distinct metrics were quantified per data set: epithelial thickness, mucosal thickness, mucosal buckling (as a measure of bronchoconstriction) and mucus contrast (an optical assessment of mucus content). Analysis of all excluding mucus contrast was performed using ImageJ (National Institute of Health, Bethesda, MD, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the clinical setting, a simple tissue surface identification algorithm would be sufficient. Our laboratory has already published automated methods for tissue surface identification, which could easily be applied to this setting (22,49).…”
Section: Discussionmentioning
confidence: 99%
“…Each autosegmented image was evaluated using texture analysis. 7 , 27 , 28 This was done using the GLCM—a statistical method of examining the spatial distributions of pixels. Four different tissue texture properties (correlation, homogeneity, contrast, and energy) were analyzed at four different angles of the GLCM (0 deg, 45 deg, 90 deg, and 135 deg), resulting in 16 unique texture variables for each image.…”
Section: Methodsmentioning
confidence: 99%